Graven ideologies Nietzsche, Derrida and Marion on modern idolatry - Benson, Bruce Ellis, 1960- (Downers Grove, IL IVP, 2002)
Includes bibliographcial refeences and index.
Keywords: Nietzsche, Friedrich, -- 1844-1900, -- philosopher; Derrida, Jacques, -- 1930-, -- philosopher; Marion, Jean-Luc -- 1946-, -- philosopher; Husserl, Edmund, -- 1859-1938, -- philosopher; Heidegger, Martin, -- 1889-1976, -- philosopher; Levinas, Emmanuel, -- 1906-1995, -- philosopher; Christianity -- philosophy; Idolatry